Multiplicity Solutions of Fractional Impulsive p-Laplacian Systems: New Result - Rafik Guefaifia; Mohamed Abdalla; Tahar Bouali; Fares Kamache; Bahri Belkacem Cherif; Ibrahim Mekawy (Journal of Function Spaces)
In this paper, the existence of multiplicity distinct weak solutions is proved for differentiable functionals for perturbed systems of impulsive nonlinear fractional differential equations. Further, examples are given to show the feasibility and efficacy of the key findings. This work is an extension of the previous works to Banach space.